2016
DOI: 10.1093/mnras/stw2960
|View full text |Cite
|
Sign up to set email alerts
|

The power and production efficiency of blazar jets

Abstract: We use published data on the power and production efficiency of jets in blazars with double radio lobes in order to compare results obtained using different methods. In order to eliminate selection effects, we use cross-matched sub-samples containing only luminous blazars. We compare the three main existing methods, namely those based on the emission of radio lobes, on spectral fitting, and on radio core shift. We find the average jet power obtained for identical samples with the radio-lobe method is ∼10 times… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 50 publications
7
57
1
Order By: Relevance
“…However, we need to be cautious and take into account uncertainties in our measurements. For example, in our treatment we do not consider electron positron pairs, which, if present, would reduce the estimated jet power by a factor n e /n p (n e = n e + + n e − , see Pjanka et al 2017). Nevertheless, to avoid the Compton Rocket effect that would otherwise break the jet (see Ghisellini & Tavecchio 2010), the number of pairs could not outnumber by a large amount the number of protons.…”
Section: Discussionmentioning
confidence: 99%
“…However, we need to be cautious and take into account uncertainties in our measurements. For example, in our treatment we do not consider electron positron pairs, which, if present, would reduce the estimated jet power by a factor n e /n p (n e = n e + + n e − , see Pjanka et al 2017). Nevertheless, to avoid the Compton Rocket effect that would otherwise break the jet (see Ghisellini & Tavecchio 2010), the number of pairs could not outnumber by a large amount the number of protons.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption is crucial and often leads to the total jet power in powerful FSRQs to exceed L Edd (e.g., Ghisellini et al 2014). Considering the presence of the electron-positron pairs would reduce the budget of the jet power (see, e.g., Madejski et al 2016;Pjanka et al 2017 L disk γ-ray loud γ-ray quiet Figure 10. Distributions of various jet powers considering twosided jets.…”
Section: Doppler and The Bulk Lorentz Factorsmentioning
confidence: 99%
“…But the efficiency of the photohadronic process depends on the photon density in the blazar jet. In a normal jet, the photon density is low, which makes the process inefficient [20]. However, it is assumed that during the flaring the photon density in the inner jet region can go up so that the Δ-resonance production is moderately efficient.…”
Section: Photohadronic Modelmentioning
confidence: 99%
“…Cao et al [18] have shown that the interaction of high energy protons with the synchrotron photons in the jet can produce γ -rays from π 0 decay and can explain the multi-TeV emission from 1ES 1011-232. Also Zdziarski et al [19,20] have used the hadronic model to explain the broad band spectra of radio-loud AGN. However, both the above scenarios require super Eddington luminosity in protons to explain the multi-TeV emission.…”
Section: Introductionmentioning
confidence: 99%